Automatic oral proficiency assessment of second language speakers of South African English - Muller, Pieter F.de V. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.